Resposta:
Explicação passo a passo:
A)
[tex]\left[\begin{array}{ccc}2&6\\7&5\end{array}\right] =\\[/tex]
2*6 -(7*6) = 12 - 42 = - 30
B)
[tex]\left[\begin{array}{ccc}-4&6\\-2&10\end{array}\right] =[/tex]
-4*10 - ( -2*6)= -40 -(-12)= -40 +12= -28
C)
[tex]\left[\begin{array}{ccc}-8&-5\\-2&-3\end{array}\right] =[/tex]
-8*(-3) - ( -2*(-5))= -18 -( 15) = -18 - 15 = -33
D)
[tex]\left[\begin{array}{ccc}x&4\\3&2\end{array}\right] =5[/tex]
x*2 - ( 4 *3) =5
2x - 12 =5
2x =12 +5
2x =17
x = [tex]\frac{17}{2}[/tex]
E)
[tex]\left[\begin{array}{ccc}-5&x\\-3&2\end{array}\right]= -4[/tex]
-5*2 -( x*(-3)) = -4
-10 -( -3x)= -4
-10 +3x = -4
3x = 10 -4
3x = 6
x = [tex]\frac{6}{3}[/tex]
x= 2
F)
[tex]\left[\begin{array}{ccc}x+1&10\\-4&3\end{array}\right] =2[/tex]
(x+1)*3 - (10* (-4))=2
3x +3 -(-40) = 2
3x+ 3 +40 =2
3x +43 =2
3x = -43 +2
3x = 41
x = [tex]\frac{41}{3}[/tex]
G)
[tex]\left[\begin{array}{ccc}2&4&5\\3&2&1\\0&3&4\end{array}\right] =[/tex]
[tex]\left[\begin{array}{ccc}2&4&5\\3&2&1\\0&3&4\end{array}\right] \begin{array}{ccc}2&4\\3&2\\0&3\end{array}\right]=[/tex]
2*2*4 +4*1*0 + 5*3*3 -( 5*2*0 + 2*1*3 + 4*3*4)
16 + 0 + 45 -( 0 + 6 + 48)
61 - 54
7
H)
[tex]\left[\begin{array}{ccc}-2&5&-1\\-3&-1&-2\\-4&1&5\end{array}\right] =\\[/tex]
[tex]\left[\begin{array}{ccc}-2&5&-1\\-3&-1&-2\\-4&1&5\end{array}\right] \begin{array}{ccc}-2&5\\-3&-1\\-4&1\end{array}\right] =\\[/tex]
-2*(-1)*5 + 5*(-2)*(-4) + -1*(-3)*1 -( -1*(-1)*(-4) + ((-2)*(-2)*1)+ 5*(-3)*5)
10 + 40 +3 -( -4 + 4 -45)
53 - (-45)
53 +45
98